1999
DOI: 10.1103/physrevlett.82.5341
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation Effects on the Superconductor-Insulator Transition in 2D Superconductors

Abstract: Results on the superconductor to insulator transition in two-dimensional films are analyzed in terms of coupling of the system to a dissipative bath. Upon lowering the temperature the parameter that controls this coupling becomes relevant and a wide range of metallic phase is recovered.PACS numbers: 73.40.Hm Quantum phase transitions (QPT) continue to attract intense theoretical and experimental interest. These transitions -where changing an external parameter in the Hamiltonian of the system induces a tra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

39
285
1
4

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(329 citation statements)
references
References 25 publications
39
285
1
4
Order By: Relevance
“…Similar crossover behavior is observed in Si MOSFET, 3 and amorphous metal films of InO x , 5 MoGe, 7 and Bi. 8 The value of H c (≈ 25 kOe) for Bi-MG is almost the same as that for Si MOSFET 3 and amorphous MoGe film.…”
Section: E Field Induced Metal-semiconductor Transitionsupporting
confidence: 58%
See 1 more Smart Citation
“…Similar crossover behavior is observed in Si MOSFET, 3 and amorphous metal films of InO x , 5 MoGe, 7 and Bi. 8 The value of H c (≈ 25 kOe) for Bi-MG is almost the same as that for Si MOSFET 3 and amorphous MoGe film.…”
Section: E Field Induced Metal-semiconductor Transitionsupporting
confidence: 58%
“…8 The value of H c (≈ 25 kOe) for Bi-MG is almost the same as that for Si MOSFET 3 and amorphous MoGe film. 7 Note that the Zeemann energy gSµ B H at 25 kOe corresponds to a thermal energy k B T H with T H = 1.7 K, where g = 2 and S = 1/2. The temperature T H is slightly lower than T c (= 2.48 K) for the superconductivity.…”
Section: E Field Induced Metal-semiconductor Transitionmentioning
confidence: 99%
“…Instead we observe always a saturation or, upon applied field, a weak logarithmic increase of the resistivity decreasing temperature [16]. The saturation for T → 0 in the insulating side of the transition has been reported for various 2D systems as, for example, in Mo-Ge films [12], GaAs/AlGaAs heterostructures [17] and Josephson junction arrays [18]. There is no consent on the origin of this saturation.…”
mentioning
confidence: 93%
“…B||c-axis. Based on magnetization data [2] and the found 2D scaling similar to that in the MIT of Si-MOSFETs (metal-oxide-semiconductor field-effecttransitor) [11], Mo-Ge [12] and Bi-films [13], the MIT in graphite has been interpreted in terms of superconducting fluctuations [1,3]. It has been shown that the density of states at the Fermi level is enhanced through topological disorder, thus leading to the possible occurrence of localized ferromagnetism and superconductivity [7].…”
mentioning
confidence: 99%
“…Interesting new developments in this problem with references to substantial earlier work may be found in [176,177,247]. The problem of transitions in Josephson arrays [247] is a variant of such problems.…”
Section: Aim and Scope Of This Papermentioning
confidence: 99%